Identity and Substrate Specificity of Reductive Dehalogenases Expressed in Dehalococcoides-Containing Enrichment Cultures Maintained on Different Chlorinated Ethenes - Liang, Xiaoming (Appl Environ Microbiol, 2015)
Many reductive dehalogenases (RDases) have been identified in organohalide-respiring microorganisms, and yet their substrates, specific activities, and conditions for expression are not well understood. We tested whether RDase expression varied depending on the substrate-exposure history of reductive dechlorinating communities. For this purpose, we used the enrichment culture KB-1 maintained on trichloroethene (TCE), as well as subcultures maintained on the intermediates cis-dichloroethene (cDCE) and vinyl chloride (VC). KB-1 contains a TCE-to-cDCE dechlorinating Geobacter and several Dehalococcoides strains that together harbor many of the known chloroethene reductases. Expressed RDases were identified using blue native polyacrylamide gel electrophoresis, enzyme assays in gel slices, and peptide sequencing. As anticipated but never previously quantified, the RDase from Geobacter was only detected transiently at the beginning of TCE dechlorination. The Dehalococcoides RDase VcrA and smaller amounts of TceA were expressed in the parent KB-1 culture during complete dechlorination of TCE to ethene regardless of time point or amended substrate. The Dehalococcoides RDase BvcA was only detected in enrichments maintained on cDCE as growth substrates, in roughly equal abundance to VcrA. Only VcrA was detected in subcultures enriched on VC. Enzyme assays revealed that 1,1-DCE, a substrate not used for culture enrichment, afforded the highest specific activity. trans-DCE was substantially dechlorinated only by extracts from cDCE enrichments expressing BvcA. RDase gene distribution indicated enrichment of different strains of Dehalococcoides as a function of electron acceptor TCE, cDCE, or VC. Each chloroethene reductase has distinct substrate preferences leading to strain selection in mixed communities.